2018
DOI: 10.1002/fsn3.646
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐induced changes in structural and physicochemical properties of β‐lactoglobulin

Abstract: Effect of ultrasound treatment on the physicochemical properties and structure of β‐lactoglobulin were investigated. β‐Lactoglobulin was treated with ultrasound at different amplitudes, temperatures, and durations. The surface hydrophobicity and free sulfhydryl group of β‐lactoglobulin were significantly increased after ultrasound treatment (p < .05). The maximal surface hydrophobicity and free sulfhydryl group were 5,812.08 and 5.97 μmol/g, respectively. Ultrasound treatment changed the physicochemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…2012; O'sullivan et al, 2016; Ma et al . 2018). Ultrasound also reduces the volume of proteins and therefore the surface tension, facilitating the droplet break‐up during emulsification (O’sullivan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2012; O'sullivan et al, 2016; Ma et al . 2018). Ultrasound also reduces the volume of proteins and therefore the surface tension, facilitating the droplet break‐up during emulsification (O’sullivan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Ma et al . (2018) reported that the application of ultrasound disrupts the structure of proteins, changing its functional properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RSM is a collection of mathematical and statistical techniques used to explore the influence and interaction of several independent factors (i.e., the design parameters) on the design responses [24]. Therefore, the identified relation (the response surface) shows the effects of the design parameters using a limited number of controlled experiments/simulations and design parameters can be optimized to produce the most desirable design response [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular structures of frequency responsive systems. References[58][59][60][61][62][63][64][65][66].…”
mentioning
confidence: 99%